The prevalence of malocclusion in urban Libyan schoolchildren - Bugaighis, Iman (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVE: This study aimed to explore the prevalence of malocclusion and its distribution among 12-17 year old Urban Libyan schoolchildren. MATERIALS AND METHODS: A total of 900 subjects were examined, of which 343 fulfilled the inclusion criteria; 169 males and 174 females. Molar relationship, overjet (OJ), overbite (OB), midline deviation, crossbite, and crowding/spacing were recorded. Sexual dimorphism was explored using descriptive statistics and the Chi-square tests. RESULTS: The prevalence of malocclusion was 95.6%. Class I, Class II division 1, Class II division 2 and Class III malocclusions comprised 66.5%, 21.9%, 3.5%, and 3.7% respectively of the total sample. The OJ percentage of 51% (zero-3.5 mm), 48.4% (>3.5 mm), 0.6% (≤−3.5 mm to >zero) was recorded, with no significant sex differences (P=0.225). A normal overbite, increased and open bites were observed in 39.9%, 55.1%, and 2.3% of the group respectively with no sexual dimorphism (P=0.970). Crossbite was present in 13.1% of the group, with no significant sex difference (P=0.469). Crowding in the maxillary and mandibular arches were observed in13.9%, and 12.2% respectively. Spacing occurred in 9.4% and 7.9% of the examined maxillary and mandibular arches respectively, with no significant sex difference regarding the presence of spacing/crowding in the maxillary arch (P>0.05). Males, however, had significantly more spacing and less crowding in the mandibular arch (P<0.05). CONCLUSIONS: The prevalence of malocclusion in Libyan schoolchildren is among the highest reported in the literature. Crowding is among the least reported manifestations of malocclusion.